2015
DOI: 10.1144/sp423.9
|View full text |Cite
|
Sign up to set email alerts
|

The global Hangenberg Crisis (Devonian–Carboniferous transition): review of a first-order mass extinction

Abstract: The global Hangenberg Crisis near the Devonian–Carboniferous boundary (DCB) represents a mass extinction that is of the same scale as the so-called ‘Big Five’ first-order Phanerozoic events. It played an important role in the evolution of many faunal groups and destroyed complete ecosystems but affected marine and terrestrial environments at slightly different times within a short time span of c. 100–300 kyr. The lower crisis interval in the uppermost Famennian started as a prelude with a minor eustatic sea-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
189
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(200 citation statements)
references
References 178 publications
9
189
0
2
Order By: Relevance
“…The DCB is marked by important and complex climatic changes (Streel et al, 2000;Streel & Marshall, 2006;Kaiser et al, 2015). As noticed by Maziane & Vanguestaine (1997) an important diminution in acritarch diversity, replaced by abundant prasinophytes are observed within the uppermost Famennian.…”
Section: Continental Biocrisis or Extinction Event?mentioning
confidence: 96%
See 2 more Smart Citations
“…The DCB is marked by important and complex climatic changes (Streel et al, 2000;Streel & Marshall, 2006;Kaiser et al, 2015). As noticed by Maziane & Vanguestaine (1997) an important diminution in acritarch diversity, replaced by abundant prasinophytes are observed within the uppermost Famennian.…”
Section: Continental Biocrisis or Extinction Event?mentioning
confidence: 96%
“…Contrasting viewpoints exist today concerning the effect of the Hangenberg Biocrisis on continental ecosystems (CascalesMiñana, 2014; Kaiser et al, 2015). Basing their analyses on a comprehensive family-level dataset, Cascales-Miñana (2014) concluded that there was no evidence for a great extinction event for plants at the DCB.…”
Section: Continental Biocrisis or Extinction Event?mentioning
confidence: 98%
See 1 more Smart Citation
“…The thorough and extensive reviews of Kaiser et al (2015) and Becker et al (2016) once more elucidated the global recognizable perturbations of the 'Sixth Phanerozoic Mass Extinction' during the Hangenberg crisis and concomitant sea-level changes at the 'end-Devonian sequence boundary' (Kaiser et al, 2015). Hence, it appears to be warrantable to place the base of sequence 1 at the base of the Hangenberg Sandstone.…”
Section: Sequence 1 -Latest Devonian-lower Hastarianmentioning
confidence: 99%
“…Even if the Hangenberg Crisis affected many groups significantly (Kaiser et al, 2016), conocardiids and hippocardiids survived this extinction event. Although this development was already visualized in Sepkoski's famous spindle diagram, the details were as yet hardly documented.…”
Section: The Evolutionary Perspective Of Strunian Rostroconchsmentioning
confidence: 99%